Social and economic consequences of wolf (Canis lupus) establishments in Sweden - Kvastegård, Emma (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2013)
Wildlife contributes with many benefits to humans but also brings economic costs. From being eradicated in Scandinavia the grey wolf (Canis lupus) is returning to South-Western Sweden and people are not used to its presence. In Scandinavia carnivores have to co-occur with humans in a landscape used for many different interests. Consequences of wolf establishments are e.g. competition for moose, depredation on sheep and attacks on hunting dogs. Wolf related issues are commonly highlighted in different media. People are expressing fears regarding wolves’ impact on e.g. the sheep industry, forest holding prices, house prices and the hunting activity. Fundamentally the conflict regarding wolf re-establishment might not concern the wolves per se, but rather how the local landscape is perceived (e.g. a scene for preserving cultural heritage or the conservation of species). There is an increasing urbanization trend in many parts of Europe and the intensity of a human-wildlife conflict is affected by social factors, e.g. low income affect people’s perception of vulnerability and therefore also increases resistance to acknowledged consequences pertaining to wildlife presence. Parts of Sweden’s countryside have poor opportunities for social development. This study investigated the potential impact of wolf occurrence on a number of economic interests and recreational and cultural values visible in the wolf debate in Sweden and also examined the development of socioeconomic factors that have the potential to influence the wolf debate. The study included all municipalities in Sweden divided in a wolf area and a wolf-free area. This study do not support the general magnitude of fears expressed in the recent wolf debate. However wolves probably enhance the already negative trend of number of sold hunting licenses which should be considered since the wildlife management in Sweden is based on hunters’ participation. Due to the strong symbol value of wolves, the negative socioeconomic development in the wolf area, and the underlying social factors affecting the intensity of conflict; wolves become a structural symbol of negative socioeconomic development, and thereby also enhancing the intensity of the wolf debate in Sweden. Since hunters participation is negatively affected by weak rural development and probably also wolves, it is needed to promote rural development and make wolves valuable to hunters. This study has also pointed out areas which are subjected to poor socioeconomic development and should therefore be prioritized for conflict mitigation measures in the future if wolves will spread to those areas. Thus, in Sweden with todays limited number of predation events, is social factors a more important driver of the wolf conflict than the actual direct consequences?